Coaches` encouragement of athletes' imagery use - Jedlic, B.; Hall, N.; Munroe-Chandler, K.; Hall, C. (Research Quarterly for Exercise and Sport, 2007)
To investigate whether coaches encourage their athletes to use imagery, two studies were undertaken. In the first, 317 athletes completed the Coaches` Encouragement of Athletes` Imagery Use Questionnaire. In the second, 215 coaches completed a slightly modified version of this questionnaire. It was found that coaches and athletes generally agreed on the relative frequency with which coaches encourage athletes to use imagery across the 4 Ws (i.e., where, when, why, and what). Coaches promoted imagery use more in conjunction with competition than training and injury rehabilitation, and higher-level coaches encouraged imagery use far more than their recreational counterparts. In addition, the level of athlete being coached had a major impact on how much or little coaches encouraged their athletes to use imagery. Coaches encouraged higher level athletes (i.e., international, national, varsity) to use imagery more than club and recreational athletes.